Activin A directly impairs human cardiomyocyte contractile function indicating a potential role in heart failure development - MacDonnell, Scott; Megna, Jake; Ruan, Qin; Zhu, Olivia; Halasz, Gabor; Jasewicz, Dan; Powers, Kristi; E, Hock; del Pilar Molina-Portela, Maria; Jin, Ximei; Zhang, Dongqin; Torello, Justin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Activin A has been linked to cardiac dysfunction in aging and disease, with elevated circulating levels found in patients with hypertension, atherosclerosis, and heart failure. Here, we investigated whether Activin A impacts cardiomyocyte (CM) excitation–contraction coupling mechanisms required to maintain heart function. Hydrodynamic gene delivery-mediated overexpression of Activin A in wild-type mice was sufficient to impair cardiac function, and resulted in increased cardiac stress markers (N-terminal pro-atrial natriuretic peptide) and cardiac atrophy. In human-induced pluripotent stem cell-derived (hiPSC) CMs, Activin A caused increased phosphorylation of SMAD2/3 and significantly upregulated SERPINE1 and FSTL3 (markers of SMAD2/3 activation and activin signaling, respectively). Activin A signaling in hiPSC-CMs resulted in impaired contractility, prolonged relaxation kinetics, and spontaneous beating in a dose-dependent manner. To identify the cardiac cellular source of Activin A, inflammatory cytokines were applied to human cardiac fibroblasts. Interleukin -1β induced a strong upregulation of Activin A. Mechanistically, we observed that Activin A-treated hiPSC-CMs exhibited impaired diastolic calcium handling with reduced expression of calcium regulatory genes (SERCA2, RYR2, ront). Importantly, when Activin A was inhibited with an anti-Activin A antibody, maladaptive calcium handling and CM contractile dysfunction were abrogated. Therefore, inflammatory cytokines may play a key role by acting on cardiac fibroblasts, causing local upregulation of Activin A that directly acts on CMs to impair contractility. These findings demonstrate that Activin A acts directly on CMs, which may contribute to the cardiac dysfunction seen in aging populations and in patients with heart failure.